Aberrant demethylation of the recoverin gene is involved in the aberrant expression of recoverin in cancer cells - Bazhin, Alexandr V.; De Smet, Charles; Golovastova, Marina O.; Schmidt, Jan; Philippov, Pavel P. (Experimental dermatology, 2010)
Please cite this paper as: Aberrant demethylation of the recoverin gene is involved in the aberrant expression of recoverin in cancer cells. Experimental Dermatology 2010; 19: 1023-1025. Abstract: The Ca2+-binding protein recoverin is normally specific for the retina. Recoverin aberrantly expressed in lung and melanoma tumors can trigger the host immune response followed by the development of a paraneoplastic neurological syndrome represented by cancer- and melanoma-associated retinopathy, respectively. The mechanisms, underlying the aberrant expression of recoverin in tumor cells, have remained unknown. The data obtained in this study suggest that (i) DNA methylation participates in the repression of synthesis of mRNA for recoverin in normal tissues and (ii) aberrant hypomethylation of the recoverin gene region, overlapping the promoter up-stream of the first exon and the first exon itself, is involved in the aberrant expression of recoverin in tumor cells.